AKIBAT HUKUM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 15/PUU-XII/2014 MENGENAI PEMBATALAN PUTUSAN ARBITRASE - Al Akbar, Alifyah Candra; Arsyi Mawarid, Muhammad Luthfan (Sriwijaya Journal of Private Law, 2025)
Arbitration is one of Alternative Dispute Resolution. Arbitration itself serves as a dispute resolution method, particularly for business actors within the corporate sphere. Not infrequently, the efforts to resolve such disputes lead to results that are not accepted by the petitioners, which then triggers follow-up actions. These actions culminate in a mechanism known as the annulment of the arbitration award. This thesis analyzes the legal consequences of the Constitutional Court Decision Number 15/PUU-XII/2014 on Article 70 of Law Number 30 of 1999, as well as the legal considerations of the Constitutional Court judges in Decision Number 15/PUU-XII/2014 concerning Article 70 of Law Number 30 of 1999. The research method used in this study is normative legal research, employing both legislative and case approaches. The result of this research shows that the legal consequence of the Constitutional Court Decision Number 15/PUU-XII/2014 on Article 70 of Law Number 30 of 1999 is the increased discretion of judges in deciding on the annulment of arbitration awards in court. Furthermore, the Constitutional Court judges in the ruling of MK Decision Number 15/PUU-XII/2014 declared that Article 70 is in conflict with the 1945 Constitution and has no binding legal force.